PENERAPAN AUDIT OPERASIONAL DALAM MENILAI EFEKTIVITAS DAN EFISIENSI FUNGSI PEMASARAN - Liestyoningrum, Hildha; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
In hospitality business, marketing function has important role in achieving company objectives in orderto maximize the profit. Operational audit on marketing function is an instrument to test and to assess theobjectives and marketing policies and to give the right recommendation in order to improve and to guide thehospitality party in the future. The purposes of this research are (1) to comprehend the implementation ofoperational audit of marketing function in order to improve the effectiveness and the efficiency of marketingfunction and (2) to analyze some factors which have caused the effectiveness and the efficiency of marketingfunction. The descriptive method has been employed as the data analysis technique. The qualitative analysisapproach has been applied by collecting the data which is relevant to operational audit of marketing function atHotel Istana Permata Ngagel Surabaya. The result of the research shows that the marketing department of HotelIstana Permata Ngagel Surabaya has encountered some problems i.e.: the budget of marketing cost which hasbeen determined by the company in 2013-2015 cannot be maximized due to the marketing cost which cannot berealized so it is not effective yet, the marketing cost increases every year. In 2013, the marketing cost target wasRp8,450,000. In 2014, the marketing cost target rose up to Rp10,550,000. In 2015, the marketing cost targetrose up to 12,800,000. Therefore, it is not efficient and started from 2013 to 2015 periods the sale target was notachieved so it has made the decline of corporate profit.Keywords: Operational Audit, Marketing, Effectiveness, Efficiency